Breathing techniques and warm compresses as therapy for adaptation of labor pain in the active phase of the first stage: A literature review - Palimbo, Adriana; Anisa, Fadhiyah Noor; Zulliati; Mahdiyah, Dede; Rahmah, Lailatul (Health Sciences International Journal, 2023)
Background: The active phase of the first stage of labor creates unpleasant conditions due to sensory and emotional experiences from the interaction of physiological and psychological processes. Labor pain coincides with maternal adaptation to pain. Labor pain results in uncoordinated uterine contractions, which results in a prolonged duration of the first stage of labor and impaired fetal well-being. Objective: This study aims to describe the application of a breathing technique model combined with warm compresses as an adaptation therapy for active phase I labor pain. Methods: Selected articles within five years, from 2017 to 2021. Initial research search results on the topic included 150 articles from PubMed and Google Scholar, keyword PICOS(T). The final selection stage was based on the inclusion criteria of 23 articles and eliminating the outer domains of the nine articles. Article covering JBI's critical assessment and synthesised a total of fourteen. Results: The findings of fourteen articles showed the average difference in pain scale and intensity before and after treatment. In addition to pain intensity, the results also show that pain can be adapted through these two methods, and provides a sense of comfort, reduces anxiety, and increases relaxation, especially in primigravid women. Conclusion: Obstacles appear in the phase and if the woman is in an abnormal pregnancy condition. Skilled attendants and family social support were accommodating in the success of this experiment. Practical implications and recommendations are needed to consider the length of treatment time and materials for compressed bottles of rubber or glass bottles.